Effect of water temperature on the duration of the internesting interval across sea turtle species. (December 2022) - Robinson, Nathan J.; Sanfèlix, Marta Mateo; Blanco, Gabriela S.; Clyde-Brockway, Chelsea; Hill, Jacob E.; Paladino, Frank V.; Tomás, Jesús; Tomillo, Pilar Santidrián
Abstract: Sea turtles generally lay several clutches of eggs in a single nesting season. While a negative correlation between water temperatures and the time required between constitutive nesting events (termed the internesting interval) has been previously reported in loggerhead Caretta caretta and green turtles Chelonia mydas, it is not understood whether this relationship remains constant across other sea turtle species. Here, we expanded upon these previous studies on loggerhead and green turtles by using larger sample sizes and including data from species with a wider range of body-sizes; specifically: hawksbill Eretmochelys imbricata, leatherback Dermochelys coriacea, and olive ridley turtles Lepidochelys olivacea . In total, we compiled temperature data from biologgers deployed over internesting intervals on 23 loggerhead, 22 green, 7 hawksbill, 26 leatherback and 11 olive ridley turtles from nesting sites in 8 different countries. The relationship between the duration of the internesting interval and water temperatures in green and loggerhead turtles were statistically similar yet it differed between all other turtle species. Specifically, hawksbill turtles had much longer internesting intervals than green or loggerhead turtles even after controlling for temperature. In addition, both olive ridley and leatherback turtles exhibited thermal independence of internesting intervals presumably due to the large body-size of leatherback turtles and the unique capacity of ridley turtles to delay oviposition. The observed interspecific differences in the relationship between the length of the internesting interval and water temperatures indicate the complex and variable responses that each sea turtle species may exhibit due to environmental fluctuations and climate change. Highlights: Water temperature assumed to effect internesting interval duration in sea turtles. Temperature data from biologgers deployed on 89 sea turtles across 5 species. Correlation only observed in green and loggerhead turtles. Varying effect of temperature between taxa has implications for climate change.